ANALYSIS OF FACTORS THE INFLUENCE CONSUMER BEHAVIOR ON THE ONLINE PURCHASE DECISION OF FASHION PRODUCTS DURING THE COVID-19 PANDEMIC - Dora, Yenny Maya; Maharani, Lina; Pratiwi, Devita Eka; Sulaeman, Iman, Dahlia; Pitriani, Putri Nur (CENTRAL ASIA AND THE CAUCASUS, 2004)
Even though all places have implemented health protocols, the risk of Covid-19 transmission is always there when outside the home. The Covid-19 pandemic continues to haunt us all out there. Whereas the fashion industry relies heavily on sales from physical outlets. So that the implementation of social distancing during the pandemic, makes consumers switch to online purchases. This study aims to determine the factors that influence consumer behavior towards purchasing decisions of fashion products online. This type of research is quantitative research. While the method used is descriptive and verification methods. The number of samples for this study was 100 consumers in the city of Bandung. Research data was obtained by distributing questionnaires to consumers. Then the research data obtained were processed using SPSS 24.0. The results of data processing and research analysis showed that partially psychological factors were more influential than other factors. While the test results together with cultural factors (X1), social factors (X2), personal factors (X3) and psychological factors (X4) significantly influence purchasing decisions (Y).